Tensiometer-Based Irrigation Management of Subirrigated Soilless Tomato: Effects of Substrate Matric Potential Control on Crop Performance - Montesano, Francesco F.; Serio, Francesco; Mininni, Carlo; Signore, Angelo; Parente, Angelo; Santamaria, Pietro (Frontiers in Plant Science, 2015)
Automatic irrigation scheduling based on real-time measurement of soilless substrate water status has been recognized as a promising approach for efficient greenhouse irrigation management. Identification of proper irrigation set points is crucial for optimal crop performance, both in terms of yield and quality, and optimal use of water resources. The objective of the present study was to determine the effects of irrigation management based on matric potential control on growth, plant–water relations, yield, fruit quality traits, and water-use efficiency of subirrigated (through bench system) soilless tomato. Tensiometers were used for automatic irrigation control. Two cultivars, “Kabiria” (cocktail type) and “Diana” (intermediate type), and substrate water potential set-points (−30 and −60 hPa, for “Diana,” and −30, −60, and −90 hPa for “Kabiria”), were compared. Compared with −30 hPa, water stress (corresponding to a −60 hPa irrigation set-point) reduced water consumption (14%), leaf area (18%), specific leaf area (19%), total yield (10%), and mean fruit weight (13%), irrespective of the cultivars. At −60 hPa, leaf-water status of plants, irrespective of the cultivars, showed an osmotic adjustment corresponding to a 9% average osmotic potential decrease. Total yield, mean fruit weight, plant water, and osmotic potential decreased linearly when −30, −60, and −90 hPa irrigation set-points were used in “Kabiria.” Unmarketable yield in “Diana” increased when water stress was imposed (187 vs. 349 g·plant−1, respectively, at −30 and −60 hPa), whereas the opposite effect was observed in “Kabiria,” where marketable yield loss decreased linearly [by 1.05 g·plant−1 per unit of substrate water potential (in the tested range from −30 to −90 hPa)]. In the second cluster, total soluble solids of the fruit and dry matter increased irrespective of the cultivars. In the seventh cluster, in “Diana,” only a slight increase was observed from −30 vs. −60 hPa (3.3 and 1.3%, respectively, for TSS and dry matter), whereas in “Kabiria,” the increase was more pronounced (8.7 and 12.0%, respectively, for TSS and dry matter), and further reduction in matric potential from −60 to −90 hPa confirmed the linear increase for both parameters. Both glucose and fructose concentrations increased linearly in “Kabiria” fruits on decreasing the substrate matric potential, whereas in “Diana,” there was no increase. It is feasible to act on matric potential irrigation set-points to control plant response in terms of fruit quality parameters. Precise control of substrate water status may offer the possibility to steer crop response by enhancing different crop-performance components, namely yield and fruit quality, in subirrigated tomato. Small-sized fruit varieties benefit more from controlled water stress in terms of reduced unmarketable yield loss and fruit quality improvements.